A circulating subset of iNKT cells mediates antitumor and antiviral immunity - Cui, Guangwei; Shimba, Akihiro; Jin, Jianshi; Ogawa, Taisaku; Muramoto, Yukiko; Miyachi, Hitoshi; Abe, Shinya; Asahi, Takuma; Tani-Ichi, Shizue; Dijkstra, Johannes M; Iwamoto, Yayoi; Kryukov, Kirill; et al. (Science immunology, 2022)
Invariant natural killer T (iNKT) cells are a group of innate-like T lymphocytes that recognize lipid antigens. They are supposed to be tissue resident and important for systemic and local immune regulation. To investigate the heterogeneity of iNKT cells, we recharacterized iNKT cells in the thymus and peripheral tissues. iNKT cells in the thymus were divided into three subpopulations by the expression of the natural killer cell receptor CD244 and the chemokine receptor CXCR6 and designated as C0 (CD244 CXCR6 ), C1 (CD244 CXCR6 ), or C2 (CD244 CXCR6 ) iNKT cells. The development and maturation of C2 iNKT cells from C0 iNKT cells strictly depended on IL-15 produced by thymic epithelial cells. C2 iNKT cells expressed high levels of IFN-γ and granzymes and exhibited more NK cell-like features, whereas C1 iNKT cells showed more T cell-like characteristics. C2 iNKT cells were influenced by the microbiome and aging and suppressed the expression of the autoimmune regulator AIRE in the thymus. In peripheral tissues, C2 iNKT cells were circulating that were distinct from conventional tissue-resident C1 iNKT cells. Functionally, C2 iNKT cells protected mice from the tumor metastasis of melanoma cells by enhancing antitumor immunity and promoted antiviral immune responses against influenza virus infection. Furthermore, we identified human CD244 CXCR6 iNKT cells with high cytotoxic properties as a counterpart of mouse C2 iNKT cells. Thus, this study reveals a circulating subset of iNKT cells with NK cell-like properties distinct from conventional tissue-resident iNKT cells.